Do Women on Boards affect Firm's Financial Performance? Evidence from Indian IPO Firms - Amit Kumar Singh; Shubham Singhania; Varda Sardana (Australasian Accounting, Business and Finance Journal, 2019)
The objective of this paper is to study whether the presence of women on boards affects the financial performance of firms. This study builds upon other studies that have earlier tried to determine the impact of number of women directors in Indian corporates on their financial performances, in terms of market performance index, i.e. Tobin's Q. The new Companies Act, 2013 has mandated the appointment of at least one woman director in certain classes of listed companies in India as described in Section 149(1)(b), which could possibly bring about a change in the governance and thus the financial performance of firms. The focus of this study is on finding and analysing the impact of compliance with this provision on the financial performance of IPO firms. In order to test our hypotheses, we selected 41 Indian Companies that have made an Initial Public Offer (IPO) in the recent past and have been listed on Bombay Stock Exchange during the period 2012-2016. The performance of each of these firms has been measured in terms of Tobin’s Q for 3 successive years after their listing (IPO) as well as by using two gender diversity index values- Blau Index and Shannon index. The study concluded that the proportion of women on board is insignificant and that it could not impact the financial performance of the firms. Neither has it caused any adverse impact on the performance of these firms.